A companion to Byzantine poetry - Hörandner, Wolfram; Rhoby, Andreas; Zagklas, Nikos (Brill's companions to the Byzantine world, 2019)
"This book offers the first complete overview of Byzantine poetry from the 4th to the 15th century. By bringing together 22 scholars, it explores the development of poetic trends and the interaction between poetry and society throughout the Byzantine millennium. Moreover, it discusses a wide range of issues concerning the writing and reading of poetry (such as style, language, metrics, function, and circulation). The volume focuses on the driving forces behind the vast verse production in Byzantium and beyond. It surveys a large number of texts and looks closely at their place within the social and cultural milieus of their authors. Overall, it aims to enhance our understanding of Byzantine poetry and shed light on its important place in Byzantine literary culture"--